Evaluation of Early Urgent Versus Delayed Urgent Laparoscopic Cholecystectomy in the Treatment of Acute Cholecystitis - Imran Javed, Muhammad Fahim, Naveed Akhtar Malik, Muhammad Sohaib Khan, Iram Adalat, Jahangir Sarwar Khan, Muhammad Mussadiq Khan (Journal of Rawalpindi Medical College, 2013)
Background: To compare the timing of laparoscopic cholecystectomy and injury to common bile duct (CBD) and frequency of failure (conversion rate from laparoscopic to open cholecystectomy) of early urgent versus delayed urgent laparoscopic cholecystectomy in acute cholecystitis. Methods: In this randomized controlled trial 110 patients, diagnosed as acute cholecystitis were divided into two groups for laparoscopic cholecystectomy. Those who were operated within 72 hours of admission to hospital were labeled as Early urgent laparoscopic cholecystectomy (EUC) group whereas those undergoing surgery after 72 hours to 02 weeks’ time were considered as Delayed urgent laparoscopic cholecystectomy group (DUC). Conversion rate from laparoscopic to open cholecystectomy and injury to CBD were compared in two groups. Results: Out of 55 patients enrolled as EUC group, 51 were female and 4 were male patients. Mean age was 39.91 ± 10.17years where as in DUC group, there were 45 female and 10 male patients in a total of 55 patients, and the mean age was 39.76 ±11.23 years. Conversion from laparoscopic surgery to open cholecystectomy was 5.45 %(03 patients) and 12.72 %(07 patients) in EUC and DUC groups respectively. The overall conversion rate was 9.09%. Obscure anatomy and adhesions were the cause of conversion. There was no statistical significance between conversion rates of the two groups. (p = 0.185) .There was no bile duct injury detected in EUC group whereas 03 patients had a bile leak in their drains detected on first post-operative day, and was managed conservatively. None of these patients required surgical intervention. No statistical significance was found between the CBD injury in two groups. (p= 0.079) Conclusion: Acute cholecystitis should be managed by laparoscopic cholecystectomy regardless of the time elapsed since the start of symptoms. There is no statistical significance of CBD injury or conversion rate from laparoscopic to open cholecystectomy associated with the timing of surgical intervention in the case of acute cholecystitis.